2021
DOI: 10.1074/mcp.ra120.002353
|View full text |Cite
|
Sign up to set email alerts
|

Global Lysine Acetylation and 2-Hydroxyisobutyrylation Profiling Reveals the Metabolism Conversion Mechanism in Giardia lamblia

Abstract: A metabolism conversion occurs in Giardia lamblia.• Glucose is not the only source of energy for G. lamblia.• Kac and Khib provides insight into metabolism conversion mechanism in G. lamblia.• Findings provide useful information of the evolutionary rule from prokaryote to eukaryote.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…That meaning that the Khib of ENO1 play an important role of regulating of cellular glycolysis and cell growth (48). Previous studies have shown that phosphoglycerate kinase (pgK) of metabolism enzymes play an important role of regulating the glycolytic process and glucose metabolism (68)(69)(70). Enhancing pgK modification of ENO1K343 causes the decreasing of enzyme activities of ENO1 (61).…”
Section: Post-translational Modifications Of Eno1 Play An Important Role In the Function Change Of Eno1mentioning
confidence: 99%
“…That meaning that the Khib of ENO1 play an important role of regulating of cellular glycolysis and cell growth (48). Previous studies have shown that phosphoglycerate kinase (pgK) of metabolism enzymes play an important role of regulating the glycolytic process and glucose metabolism (68)(69)(70). Enhancing pgK modification of ENO1K343 causes the decreasing of enzyme activities of ENO1 (61).…”
Section: Post-translational Modifications Of Eno1 Play An Important Role In the Function Change Of Eno1mentioning
confidence: 99%
“…Several post-translational modifications (PTMs) of proteins are reportedly involved in Giardia encystation, namely deacetylation [ 58 ] and phosphorylation [ 59 ]. Consequently, several proteomic studies have aimed to characterise the PTMs of proteins in G. duodenalis [ 4 , 11 , 15 , 60 , 61 , 62 ], such as the role of G. duodenalis DHHC proteins in protein S-palmitoylation during Giardia encystation [ 61 ]. Specifically, Merino et al (2014) reported that nine DDHC proteins were identified in trophozoites and encysting cells of G. duodenalis , and concluded that the presence of DDHC proteins in the encysting parasites indicates that the protein S-palmitoylation is maintained and involved in cell signalling, protein-sorting, and protein exporting throughout encystation.…”
Section: Applications Of Proteomicsmentioning
confidence: 99%
“…Another recent study, by Zhu et al (2021), that utilised a global approach in investigating metabolic conversion mechanisms of G. duodenalis under stress revealed a total of 2999 lysine acetylation (Kac) sites on 956 proteins and 8877 2-hydroxyisobutyrylation (Khib) sites on 1546 proteins when G. duodenalis was under sugar starvation [ 62 ]. The authors noted a temporal reduction in both Kac and Khib proteins when G. duodenalis was cultured under sugar starvation for 72 h, indicating their involvement in energy conversion metabolism.…”
Section: Applications Of Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khib adds a large 2-hydroxyisobutyryl group to the lysine residue, which increases the size of the lysine side chain, abolishes the positive charge, and introduces a hydroxyl group that enables the modified lysine to form hydrogen bonds with other molecules [1]. As a result, Khib can influence various biological processes, such as the regulation of gene expression, energy metabolism, protein translation, and secondary metabolism [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%